The Effectiveness of Mulligan Mobilization With Movement (MWM) in Lateral Epicondylitis: a Critical Review - Zami, Muhammad Dimas Zam; Pristianto, Arif; Nasrullah, Nasrullah (Universitas Muhammadiyah Surakarta, 2023)
Background: Lateral epicondylitis is a common injury in tennis and badminton players. This lateral epicondylitis condition generally appears in any individual or an activity that requires a circular motion of the forearm. These movements when performed repeatedly accompanied by loading when gripping or wrist extension can increase the risk of lateral epicondylitis. Complaints that arise in the condition of lateral epicondylitis include experiencing pain in the lateral elbow and weakness of the wrist or wrist. Mulligan mobilization with movement is a modern technique developed by Mulligan to treat musculoskeletal complaints such as lateral epicondylitis. Objective: This study aims to determine the effectiveness of giving mulligan mobilization with movement in lateral epicondylitis conditions. Method: The research method used is critical review. This method is used to analyze, summarize or evaluate an action. Critical review is done by evaluating the selected articles using the PEDro Scale. Results: The results of the review of the five articles that have been screened including the inclusion criteria found that various modalities were used, either singly or in combination. This Mulligan mobilization with movement can reduce pain and improve functional ability in the elbow. Conclusion: Mulligan mobilization with movement is effective and can be used as an alternative choice in the treatment of lateral epicondylitis. Mobilization with movement techniques, can be combined with several therapeutic measures such as conventional treatments and exercise to get optimal results. Keywords: Mulligan Technique, mobilization with movement, MWM, lateral epicondylitis, tennis elbow